FE-SEM/EDX Based Zinc Mobilization Analysis of Burkholderia cepacia and Pantoea rodasii and Their Functional Annotation in Crop Productivity, Soil Quality, and Zinc Biofortification of Paddy - Upadhayay, Viabhav Kumar; Singh, Ajay Veer; Khan, Amir; Singh, Jyoti; Pareek, Navneet; Raghav, Alok (Frontiers in Microbiology, 2022)
The experimental study was contrived to characterize two zinc solubilizing bacteria (ZSB) namely BMRR126 and BMAR64 and their role in zinc (Zn) biofortification of rice. These bacteria solubilized Zn profoundly determined qualitatively by halo-zone formation on a solid medium and quantitatively in liquid broth by AAS and SEM-EDX. The lowering in pH and contact angle assessment of the liquid broth unveiled the establishment of the acidic conditions in a medium suitable for Zn solubilization. The characterization of both isolates on the basis of 16S rRNA gene analysis were identified as Burkholderia cepacia and Pantoea rodasii, respectively. These strains were also found to have some plant probiotic traits namely phosphate solubilization, production of siderophore, indole acetic acid, exopolysaccharide (EPS) and ammonia. The field experiments were performed at two diverse locations and under all treatments, the simultaneous use of BMRR126 and BMAR64 with ZnO resulted in the highest growth and productivity of the paddy crop. The utmost Zn achievement in the grain was estimated in treatment (T9) (25.07 mg/kg) containing consortium of BMRR126 and BMAR64 along with zinc oxide for the Terai region. While treatment containing single ZSB bioinoculant BMRR126 (T7) showed an elevated Zn amount in rice grain (33.25mg/kg) for the Katchar region. The soil parameters (pH, EC, organic carbon, NPK, available Zn and dehydrogenase activity) also positively influenced under all bacterial treatments compared to uninoculated control. Our study clearly accentuates the need of zinc solubilizing bacteria to provide the benefits of Zn-biofortification in different regions.